VARIABILITY SPATIAL AND TEMPORAL SEA SURFACE TEMPERATURE AND CHLOROPHYLL-a CONCENTRATION USING AQUA MODIS IMAGERY SATELLITE AT WEST SUMATERA AQUATIC - Muslim '; Usman '; Alit Hindri Yani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Sea Surface Temperature (SST) and chlorophyll-a factor were often used in determining fishing ground area. This research aimed to know variability spatial and temporal SST and chlorophyll-a at west sumatera aquatic. This research use the data of SST and chlorophyll recorded by satelite of aqua modis with spatial resolution 4 km and temporal resolution monthly data. The high mean value of SST was found on first switchover season with value 30,330C and the low mean value of SST was found on west season and second switchover season with value 29,630C. The high mean value of chlorophyll-a was found on second switchover season with value 0,16 mg/m3 and the low mean value of chlorophyll-a was found on east season with value 0,13 mg/m3.Keyword : Variablity, SST, Chlorophyll-a, Spatial, Temporal, Aqua MODIS, West Sumatera